2023
DOI: 10.1159/000530784
|View full text |Cite
|
Sign up to set email alerts
|

Association of Alopecia Areata with Sensorineural Hearing Loss: A Systematic Review and Meta-analysis

Abstract: Background: Immune-mediated melanocyte-related pathogenesis in alopecia areata (AA) may cause sensorineural hearing loss (SNHL). However, the relation between AA and SNHL has been unclear. Therefore, we aimed to investigate this association between AA and SNHL. Methods: We performed a systematic review and searched MEDLINE and Embase on July 25, 2022 for cross-sectional, case-control, or cohort studies that examined the association of AA with SNHL. The Newcastle–Ottawa Scale was used to evaluate their risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…A study based on claims data from the USA reported an association between the AT/AU subtype and higher occurrence of some autoimmune and inflammatory conditions [ 27 ]. Sensorineural hearing loss is a known disease manifestation of several autoimmune disorders and has been reported in patients with AA [ 28 ]. With regards to the higher prevalence of patients with AT/AU with a history of surgery in the previous 6 months in the present study, postsurgical stress could be associated with hair loss and thus it cannot be ruled out that some AA diagnoses represent misdiagnosed telogen effluvium.…”
Section: Discussionmentioning
confidence: 99%
“…A study based on claims data from the USA reported an association between the AT/AU subtype and higher occurrence of some autoimmune and inflammatory conditions [ 27 ]. Sensorineural hearing loss is a known disease manifestation of several autoimmune disorders and has been reported in patients with AA [ 28 ]. With regards to the higher prevalence of patients with AT/AU with a history of surgery in the previous 6 months in the present study, postsurgical stress could be associated with hair loss and thus it cannot be ruled out that some AA diagnoses represent misdiagnosed telogen effluvium.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the underlying mechanisms, the influence of melanocytes on the structure and function of the auditory system has been considered as a plausible one 89 . Current evidence suggests that follicular melanocytes may be an important target in the autoimmune process of AA 90 ; additionally, melanocytes are located in the spiral ligament and in the stria vascularis of the inner ear, where they play a crucial role in the potassium channels that regulate cochlear potential and maintain auditory signaling 38 . Therefore, autoimmune‐mediated destruction of melanocytes in the cochlea by inflammatory responses and oxidative stress may cause impaired auditory function.…”
Section: Discussionmentioning
confidence: 99%
“…However, the worse outcome of the disease is indicated by a positive family history, childhood onset of AA, nail involvement, atopic dermatitis, and the existence of chronic lesions lasting longer than 12 months [ 16 ]. In addition to its impact on hair loss, AA is associated with the development of concurrent and potentially disease-modifying disorders, including atopic diatheses, like allergic rhinitis and particularly atopic dermatitis, appearing in more than 30% of AA patients [ 17 , 18 ]; autoimmune diseases such as vitiligo and psoriasis [ 19 ]; hidradenitis suppurativa [ 20 ]; thyroid disorders [ 21 ]; lupus erythematosus [ 6 ], pernicious anemia and celiac disease [ 22 ]; irritable bowel syndrome [ 23 ]; insulin resistance [ 24 ]; migraine [ 25 ]; audiologic and ophthalmic abnormalities [ 26 , 27 , 28 , 29 ]; and psychiatric comorbidities such as sleep disorders, anxiety, alexithymia, social phobia, and paranoid and major depression disorder [ 1 , 30 , 31 , 32 ]. AA disfigures the person’s appearance and significantly impacts self-esteem, sociocultural identity, and patient QoL [ 2 , 33 ].…”
Section: Introductionmentioning
confidence: 99%